Caracterização química e avaliação dos potenciais antimicrobiano, inseticida e citotóxico de óleos essenciais obtidos de Myrcia spp. (myrtaceae) ocorrentes em ecossistema de terra firme (Amazônia) - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
The Myrtaceae family has 132 genera distributed in 5,760 species present in Australia, Southeast Asia, tropical and temperate America. In Brazil, it presents 1,018 species in 23 genera. Myrcia D.C is one of the largest genera with 282 species present in almost all territory, of which 220 are endemics. Its species are used in Brazilian popular medicine, with emphasis on Myrcia spp., which are used by the traditional population of the Amazon as astringents, diuretics, hypoglycemics, antihemorrhagics, antioxidants and in the treatment of hypertension and ulcers. The present study has evaluated the chemical composition of the essential oils of 13 species of Myrtaceae (Myrcia spp., Marlierea sp. and Calyptranthes sp.) from the Terra Firme ecosystem (Amazon). In addition, the cytotoxic, antibacterial, bacteriostatic, antifungal and larvicidal potentials of these oils have been described. Twenty-seven samples belonging to these thirteen species (18 individuals of 11 species of Myrcia, one of Marlierea caudata and one of Calyptranthes spruceana) were collected from the Adolpho Ducke Forest Reserve, EMBRAPA (Manaus) and the PANC site (Manaus). Its essential oils were obtained by hydrodistillation, dried and stored under refrigeration. The chemical characterization was carried out by means of CG-DIC and CG-EM analysis. The Arithmetic Indexes and the Spectral Similarity Indexes were obtained, whose results were compared with those described in the main databases. The mean chemical characterization of these oils was 95%, totaling 336 compounds identified, of which 34 have been abundant (50.7 to 96.17%). The most frequent and, in some cases, the most frequent components are: (E)-caryophyllene, δ-cadinene, Espatulenol, α-Copaene, β-elemene, α-humulene, Caryophyllene oxide, β-selinene, α-muurolene and α–cadinol (42.73% of nonoxygenated sesquiterpenes and 36.98% of oxygenated sesquiterpenes). This chemical variability is common to Myrcia species of other Brazilian ecosystems/biomes. Of the seven pairs of Myrcia individuals collected in distinct periods (dry and rainy), 242 compounds were identified, of which 125 were common, 41 and 76 of which were unique to the rainy and dry periods, respectively. Essential oils of the dry period have exhibit greater chemical variability. In addition, the chemical variability of the essential oils of Myrcia spp. of this ecosystem has been described by 51 cyclization pathways. Of these routes, thirteen have a high frequency (above 50%), four of which are the most prominent ones (Cariofilan, Cadinano, Aromadendrano and Eudesmano). The chemical results of this study have revealed a clear agreement of the chemical composition of Marlierea caudata with the chemistry composition of Myrcia spp.. On the other hand, this observation is not clearly evident for C. spruceana. Moreover, It should be noted that the chemical composition of the essential oils of M. magnoliifolia, M. minutiflora, M. fenestrata, M. amapensis and Marlierea caudata have been described for the first time. As for toxicity to cancer cells (Skmel 3 and ACPO2) and normal cells (MRC5), M. minutiflora presents moderate activity for human melanoma (Skmel 3) and gastric adenocarcinoma (ACPO2) as well as cytotoxic to non-neoplastic fibroblasts (MRC5). M. citrifolia, M. minutiflora, M. paivae and M. magnoliifolia present moderate to high activity against Staphylococcus aureus. M. fallax, M. sylvatica, M. paivae and C. spruceana present moderate activity against Staphylococcus aureus. As for the bacteriostatic action, all species tested have shown moderate to high activity against Pseudomonas aeroginosas. In relation to the insecticidal activity, M. citrifolia, M. bracteata, M. fenestrata, M. amazonica, M. paivae and C. spruceana are active, since after 24 h the mortality percentage of Aedes aegypti larvae was 100% in 25 mg.L- 1 of essential oil. Furthermore, the use of chemometric tools in this study has shown it possible to observe the segregation of samples by major terpene groups and their most influential cyclic pathways, whose substances of major relevance in this model have been (E)-Caryophyllene, δ-Cadinene, and Espatulenol. Its pharmacological activities described in the literature should suggest that they are responsible for the biological results observed in this work. However, novel biological assays with such isolated constituents must be necessary. Therefore, with respect to the chemistry of Myrcia volatile constituents occurring in Terra Firme (Amazonia), the present study has been evidenced very characteristic Amazonian chemotypes and without similarity with other species collected outside the region, which leads us to conclude how much to must be studied from the precious Amazonian biodiversity.
Keywords: Quimiometria; Citotoxicidade; Antibacteriano; Bacteriostático; Antifúngico; Biofármacos; Larvicida; Bioinseticida; Chemometric; Cytotoxicity; Antibacterial; Bacteriostatic; Antifungal; Biopharmaceutical; Larvicide; Bioinsecticide; CIÊNCIAS EXATAS E DA TERRA: QUÍMICA